2021
DOI: 10.3390/app11093837
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Sex Hormone-Disruption Effects of Two Novel Brominated Flame Retardants (DBDPE and BTBPE) in Male Zebrafish (Danio rerio) and Two Human Cell Lines (H295R and MVLN)

Abstract: Decabromodiphenyl ethane (DBDPE) and 1,2-bis(2,4,6-tribromo-phenoxy) ethane (BTBPE) are novel brominated flame retardants (NBFRs) and have been detected in variety of environment and biota. Although sex endocrine-disrupting potential has been suggested in experimental studies, their adverse effects on sex steroid hormones and underlying mechanisms are largely unclear. The purpose of the present study is to investigate the sex hormone-disrupting effects of two NBFRs using in vivo and in vitro models together. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…For example, the bromine-containing molecule decabromodiphenyl ethane (DBDPE) greatly facilitates the gas phase activity of this flame retardant. Several studies suggested that DBDPE does not release the toxic and carcinogenic polybrominated dibenzo-p-dioxin (PBDD) and polybrominated dibenzofuran (PBDF) gases during combustion due to the absence of ether linkages [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the bromine-containing molecule decabromodiphenyl ethane (DBDPE) greatly facilitates the gas phase activity of this flame retardant. Several studies suggested that DBDPE does not release the toxic and carcinogenic polybrominated dibenzo-p-dioxin (PBDD) and polybrominated dibenzofuran (PBDF) gases during combustion due to the absence of ether linkages [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that numerous compounds present in the environment act as hormone mimics and interfere with the reproductive status of vertebrates through effects ranging from alterations in plasma reproductive hormone levels to sterility [8]. An alteration in steroid hormone synthesis is an important biological response from a toxicological standpoint [9][10][11]. This is because the biological effects of pollutant exposure in organisms can be investigated through several molecular and biochemical biomarkers reflecting the onset of various cellular alterations [12,13].…”
Section: Introductionmentioning
confidence: 99%